2021
DOI: 10.2147/ijgm.s306543
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in General Medicine Departments of University Hospitals in Japan

Abstract: Purpose The training of generalist physicians in university hospitals needs to emphasize development of their research role in order to continue improving their research capacity and their standing in academic hospitals in Japan. This cross-sectional descriptive study aimed to survey departments of general medicine (GM) in university hospitals in Japan to identify the research areas and themes pursued by academic generalist physicians. Patients and Methods The heads of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 13 publications
0
28
1
Order By: Relevance
“…24 Another report from Japan suggests that it is important for GMs in university hospitals to promote research work. 25 Therefore, one of the challenges GMs face is the need to develop their research work and allocate time to conduct research. In order to increase research work, it is important to have a mentor and secure time for research (25% of daily work) and to conduct it effectively.…”
Section: Discussionmentioning
confidence: 99%
“…24 Another report from Japan suggests that it is important for GMs in university hospitals to promote research work. 25 Therefore, one of the challenges GMs face is the need to develop their research work and allocate time to conduct research. In order to increase research work, it is important to have a mentor and secure time for research (25% of daily work) and to conduct it effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the main reasons Hospital Medicine has become the largest group of physicians in the United States 4 . On the downside, in publication data indexed on PubMed by hospitalists that the author (TW) previously published, the quality and safety area of healthcare and the health service area accounts for about 40% of the world's total of the publication by hospitalists 5 . However, a recent survey conducted by the authors found that the combined research topics of Japanese university hospital general practitioners accounted for less than 2%, and our another study indicated only about 8% of the recent papers published by Japanese general medicine physicians in PubMed between 2015 and 2020 focused on QI and safety area and the health services.…”
Section: Figurementioning
confidence: 99%
“…However, a recent survey conducted by the authors found that the combined research topics of Japanese university hospital general practitioners accounted for less than 2%, and our another study indicated only about 8% of the recent papers published by Japanese general medicine physicians in PubMed between 2015 and 2020 focused on QI and safety area and the health services. This indicates Japanese academic general physicians need to be more active in producing healthcare quality and safety research 4,5 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations